Functional connectivity experiments reflect routine movement behavior of a tropical hummingbird species. Issue 8 (1st December 2014) - Volpe, Noelia L.; Hadley, Adam S.; Robinson, W. Douglas; Betts, Matthew G.
Abstract : Translocation experiments, in which researchers displace animals and then monitor their movements to return home, are commonly used as tools to assess functional connectivity of fragmented landscapes. Such experiments are purported to have important advantages of being time efficient and of standardizing "motivation" to move across individuals. Yet, we lack tests of whether movement behavior of translocated birds reflects natural behavior of unmanipulated birds. We compared the routine movement behavior of a tropical hummingbird, the Green Hermit ( Phaethornis guy ), to that of experimentally translocated individuals. We tested for differences in site selection patterns during movement at two spatial scales (point and path levels). We also compared movement rates between treatments. Behaviors documented during translocation experiments reflected those observed during routine movements. At the point level, both translocated and non‐translocated birds showed similar levels of preference for mature tropical forest. At the path level, step selection functions showed both translocated and non‐translocated hummingbirds avoiding movement across non‐forested matrix and selecting streams as movement corridors. Movement rates were generally higher during translocation experiments. However, the negative influence of forest cover on movement rates was proportionately similar in translocation and routine movement treatments. We report the first evidence showing that movement behavior of birds during translocation experiments is similar to their natural movement behavior. Therefore, translocation experiments may be reliable tools to address effects of landscape structure on animal movement. We observed consistent selection of landscape elements between translocated and non‐translocated birds, indicating that both routine and translocation movement studies lead to similar conclusions regarding the effect of landscape structure and forest composition on functional connectivity. Our observation that hummingbirds avoid non‐forest matrix and select riparian corridors also provides a potential mechanism for pollen limitation in fragmented tropical forest.